Theoretical perspectives and practical insights into the roles of project and product managers - Jenný Huyen Andradóttir 1990-; Sidi Zaki Ramadhan Ögmundsson 1986- (2024)
This study delves into the nuanced roles of Project and Product Managers within large, technologically driven organizations in Iceland, highlighting the distinct and overlapping responsibilities, collaboration mechanisms, and conflict resolution strategies. Through structured interviews and qualitative analysis with 7 Project Managers and 6 Product Managers, it explores how these roles are distinguished not just by their daily responsibilities but also by their strategic impact on businesses’ long-term goals. Key findings reveal that while Project Managers focus primarily on operational and execution aspects, Product Managers emphasize maximizing product value and strategic positioning in the market, often making both roles adapting their roles to align with specific organizational needs. Both roles utilize soft skills alongside formal governance processes to manage conflicts, especially when negotiating overlapping responsibilities. The research underscores the importance of clear role definitions and effective communication in facilitating collaboration and resolving conflicts, offering valuable insights into the dynamic interplay between the roles of Project and Product managers in achieving organizational objectives.